Probabilistic modeling of short survivability in patients with brain metastasis from lung cancer. Issue 3 (May 2015) - Makond, Bunjira; Wang, Kung-Jeng; Wang, Kung-Min
Highlights The use of Bayesian network to predict the short survivability of patients. The use of synthetic minority over-sampling technique to improve the sensitivity. The proposed model has the highest sensitivity among all benchmark methods.